Pengaruh Pemberian Ampas Tahu Fermentasi Dalam Ransum Terhadap Karkas Ayam Broiler - Pardosi, Untung (LPPM Universitas HKBP Nommensen, 2022)
The study is aimed at knowing the impact the slag had on the ration against the 35-day broiler carols. This study is carried out in simalingkar, denser of lucky field. The study USES 100 broiler strain of cp 707. The rations used were a mixture of several food-prepared food items in Microsoft excel programs that guide the nutritional needs of the broiler. The method used in this study is a complete random design (ral) consisting of 5 treatments of p0 = 0% p1 = 5% p2 = 10% p3 = 15% p4 = 20% and each has 4 deuteronomy consisting of 5 broiler chickens. The parameters measured are cut weights, weight of cash, percentage of cash. The data obtained from the study was analyzed with (anova). Conclusions drawn from this study suggest that the wise men knew the fermentation in the ration of the 35-day broiler carburettor (p > 0.05) against the weight of the cut, the weight of the karkas, the percentage of the kas